Aggressive Scheduling and Speculation in Multithreaded Architectures: Is it Worth its Salt? - Loew, Jason; Ponomarev, Dmitry (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
This paper investigates and quantifies the impacts of several aggressive performance-boosting techniques designed for superscalar processors on the performance of SMT architectures. First, we examine the synergy of multithreading and speculative execution. Second, we quantify the performance impact of not supporting the load-hit speculation. Finally, we consider the impact of pipelining instruction scheduling logic over two cycles. The general conclusion of our studies is that while speculative execution is still important to achieve high SMT performance, scheduler-related mechanisms can be relaxed because the pipeline bubbles created in the execution schedule of one thread are often filled by the instructions from other threads.